KONSEP KALÂLAH DALAM ALQURAN DAN PENAFSIRANNYA MENURUT SUNI DAN SYIAH IMÂMIYYAH - Evra Willya (Universitas Islam Negeri Jakarta, 2014)
Kalâlah in Alquran and Its Interpretation According to Suni and Syiah Imâmiyyah. This article is aimed to analyze the meaning of walad in the inheritance of kalâlah in Alquran. Islamic jurists have different vews in interpreting the meaning of walad in kalâlah inheritance. Walad in kalâlah inheritance gives the influence to the siblings inheritance. This article attempts to discuss critically and impartially the meaning of walad. By using comparative method, the writer analyzes the meaning of walad from the Suni and Syiah Imâmiyyah perspective. The writer concludes that there is no consensus among Islamic Scholars in interpreting the meaning of walad, by which for the Suni Scholars, the meaning of walad is only brothers of the heir, whereas for the Syiah Imâmiyyah include the heir’s sisters. This different opinion influences the regard of the two mainstreams towards the status of brother and sister in the inheritance of kalâlah.DOI: 10.15408/ajis.v14i1.1250